2004
DOI: 10.1073/pnas.0404341102
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific RING finger 1 is a bona fide ubiquitin ligase that degrades cardiac troponin I

Abstract: Muscle-specific RING finger protein 1 (MuRF1) is a sarcomereassociated protein that is restricted to cardiac and skeletal muscle. In skeletal muscle, MuRF1 is up-regulated by conditions that provoke atrophy, but its function in the heart is not known. The presence of a RING finger in MuRF1 raises the possibility that it is a component of the ubiquitin-proteasome system of protein degradation. We performed a yeast two-hybrid screen to search for interaction partners of MuRF1 in the heart that might be targets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
245
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(258 citation statements)
references
References 38 publications
12
245
1
Order By: Relevance
“…We believe that the coiled-coil region of MuRF1 is the structure required for recruiting BK-␤1 to MuRF1 because BK-␤1 can be detected in the pulldown of the MuRF1 coiled-coil region alone, but a direct protein binding experiment is required to further confirm our findings. Our results are similar to previous observations that the coiled-coil region is sufficient for MuRF1 binding to sarcomeric M-line titin and thick filament (63). Interestingly, partially deleting the RING finger domain or the family conserved region of MuRF1 interferes with the physical association with BK-␤1.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We believe that the coiled-coil region of MuRF1 is the structure required for recruiting BK-␤1 to MuRF1 because BK-␤1 can be detected in the pulldown of the MuRF1 coiled-coil region alone, but a direct protein binding experiment is required to further confirm our findings. Our results are similar to previous observations that the coiled-coil region is sufficient for MuRF1 binding to sarcomeric M-line titin and thick filament (63). Interestingly, partially deleting the RING finger domain or the family conserved region of MuRF1 interferes with the physical association with BK-␤1.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, MuRF1 interacts with the hydrophobic amino acids of "Titin repeats" (61) and myosin heavy chain in skeletal muscles (62). The coiled-coil region of MuRF1 is responsible for the binding of troponin I in cardiomyocytes (63). The MuRF family conserved region is required for the interaction with phospho-c-Jun in the heart (64).…”
Section: Discussionmentioning
confidence: 99%
“…MuRF-1 ubiquitinates myofibrillar and cytoskeleton proteins and metabolic enzymes in preparation for their subsequent breakdown in the proteasome [57][58][59][60]. In line with this role in muscle protein breakdown during fasting, we observed that MuRF-1 expression was increased substantially in the alfacalcidol group, without a change in MAFbx mRNA levels (see Fig.…”
Section: Effects Of Alfacalcidol and Muscle Fibre Atrophysupporting
confidence: 73%
“…It has also recently been reported that myocardium lacking MuRF1 expression has exaggerated cardiac hypertrophy in response to prohypertrophic stimulation [13] . More recently, some other reports have demonstrated that MuRF1 inhibits cardiac hypertrophy by degrading sarcomeric proteins that constitute the bulk of cardiomyocyte mass [30] and interfering with prohypertrophic signaling [31] . In cardiomyocytes, these processes may determine the balance between prohypertrophic and antihypertrophic signals [30] .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some other reports have demonstrated that MuRF1 inhibits cardiac hypertrophy by degrading sarcomeric proteins that constitute the bulk of cardiomyocyte mass [30] and interfering with prohypertrophic signaling [31] . In cardiomyocytes, these processes may determine the balance between prohypertrophic and antihypertrophic signals [30] . As a sensor of cellular energy status, AMPK responds to an increase in the ratio of AMP to ATP, which can be observed in response to starvation, exercise, and muscle contraction [20,32] .…”
Section: Discussionmentioning
confidence: 99%